Problematic Nature of Uang Panai in Bugis-Makassar Marriages: A Case Study in South Sulawesi Province - S. Salle; Andi Risma; Dian Eka Pusvita Azis (Golden Ratio of Law and Social Policy Review, 2026)
Indonesia possesses a vast cultural diversity, including the Bugis-Makassar ethnic group in South Sulawesi, which maintains a unique marriage tradition known as Uang Panai’. Distinct from the dowry, Uang Panai’ is a customary requirement representing a marriage endowment provided by the groom that serves as a symbol of social status, prestige, and a determinant for the success of a wedding, though its high cost often leads to canceled marriages or the occurrence of Silariang. This study aims to provide solutions to the issues surrounding the fluctuating and often exorbitant costs of Uang Panai’ through a quantitative method using frequency distribution to measure the relationship between the uncertain value of Uang Panai’ as the dependent variable and factors such as education, occupation, economic status, lineage, physical appearance, and social environment as independent variables. The results indicate that Uang Panai’ significantly influences the implementation of marriages, with its amount being determined by the aforementioned social factors, leading to the conclusion that an ideal solution requires the establishment of regional regulations as a legal framework. Consequently, this study recommends the necessity of legal counseling regarding marriage requirements and urges local governments in South Sulawesi to formulate Peraturan Daerah to provide legal certainty and moderate the implementation of this tradition.